Ideação de novos serviços : aplicação da metodologia ideatriz - Weigert, Ana Paula (2016)
In a world even more globalized, where the product comoditization has become faster, the organizations are falling back on new service development and innovation as essential ways to face competition and become differentiated in the market. Created in a recent study, the IDEATRIZ methodology includes value analysis, systematic and heuristic methods coming from TRIZ methodology in order to generate product ideas in the manufacturing field. But the actual necessity of innovation in the services field due to its importance in the economy and, the fact that TRIZ has been already applied in other fields as quality, energy and services, this study aimed to prove that IDEATRIZ methodology can be a powerful tool for services ideation. It was brought also the hypotesis that the direct use IDEATRIZ would result in lesser quality ideas that if it were be compared to the same methodology but adapted for service. Thus a research was carried out to validate these hypothesis. The IDEATRIZ methodology was applied directly and adapted in several workshops to generate service ideias and the results were compared. The raised suggestions collected in direct application were used to adapt the methodology. As result of comparison between original and adapted IDEATRIZ, it was obtained increasing the quality of generated ideas and the ease of use of the methodology adapted by including examples of services in heuristics and inventive principles phases. The contribution of this research was to open the field of IDEATRIZ methodology for service innovation as a tool to support creative solutions to generate new services.